Free time of elderly people in terms of physical activity - D. Czarnecki; D. Skalski; I. Grygus (Nicolaus Copernicus University in Toruń, 2022)
Gerontological issues will gain more and more recognition, both in the social and medical aspect. The reason for this is the sharp increase in the percentage of the elderly population, which is related to a decline in birth rates on the one hand and an increase in life expectancy on the other. The aging of the population of Europe and Poland is probably the most important health and socio-political challenge in the coming years. In 2050, people aged 60-79 are expected to make up a quarter of the entire population of the European Union. Maintaining the appropriate level of health, independence and independence of the elderly becomes a great challenge. This is not only a public health challenge, but also a huge socio-economic problem. A typical situation in old age is the occurrence of several diseases at the same time. In addition, the situation is complicated by the procedure of a number of degenerative changes affecting almost all systems and functions of the system, deteriorating the possibility of functioning and rehabilitation. Taking up issues related to seniors becomes important for at least several reasons. The most important ones include: the increasing number of elderly people, the widespread cult of a financially efficient and independent person (completely different from the geriatric reality), the need to educate professionals to help or support those in need, and the need for mental changes in society regarding the aging process and old age itself. The aim of this article is to present the problem of leisure time of elderly people from the perspective of physical activity. The starting point for the considerations was the explanation of the concepts of "old age" and "aging". Next, the most important issues concerning human activity in late adulthood are presented and the main assumptions of the theory of activity are presented. Then the concept of free time was defined, the features of free time activity were discussed, and the functions of free time were also indicated. Attention was also paid to the structure of seniors' time budget and the types of free-time activity that dominate among them. Next, the problem of free time of old people is presented in the context of the theory of activity, paying particular attention to the issues related to the activation of seniors.